Chromosome-Level Genome Assembly Reveals Significant Gene Expansion in the Toll and IMD Signaling Pathways of Dendrolimus kikuchii - Zhou, Jielong; Wu, Peifu; Xiong, Zhongping; Liu, Naiyong; Zhao, Ning; Ji, Mei; Qiu, Yu; Yang, Bin (Frontiers in Genetics, 2021)
A high-quality genome is of significant value when seeking to control forest pests such as Dendrolimus kikuchii, a destructive member of the order Lepidoptera that is widespread in China. Herein, a high quality, chromosome-level reference genome for D. kikuchii based on Nanopore, Pacbio HiFi sequencing and the Hi-C capture system is presented. Overall, a final genome assembly of 705.51 Mb with contig and scaffold N50 values of 20.89 Mb and 24.73 Mb, respectively, was obtained. Of these contigs, 95.89% had unique locations on 29 chromosomes. In silico analysis revealed that the genome contained 15,323 protein-coding genes and 63.44% repetitive sequences. Phylogenetic analyses indicated that D. kikuchii may diverged from the common ancestor of Thaumetopoea. Pityocampa, Thaumetopoea ni, Heliothis virescens, Hyphantria armigera, Spodoptera frugiperda, and Spodoptera litura approximately 122.05 million years ago. Many gene families were expanded in the D. kikuchii genome, particularly those of the Toll and IMD signaling pathway, which included 10 genes in PGRP, 19 genes in MODSP, and 11 genes in Toll. Moreover, in the larval developmental stages of D. kikuchii, the lowest and highest expressions of genes of the Toll and IMD signal pathways were observed in the fourth and the fifth instars, respectively. The findings from this study will help to elucidate the mechanisms involved in protection of D. kikuchii against foreign substances and pathogens, and may highlight a potential channel to control this pest.